Migration Into the Myometrium of the IUD Associated with a Painful Ovarian Cyst - Dagbesse Elysee Boko Dagoun; Yaya Samake; Michelle Menin-Messou; Clausen Georgie M’Bro; Narcisse Kouadio Kouadio; Lydie Estelle Djanhan (European Scientific Journal, ESJ, 2025)
The intrauterine device (IUD) or IUD is the most widely used contraceptive method in the world. Its secondary migrations are varied but rare when it comes to the myometrium according to the literature. We report a clinical case of migration of the IUD into the myometrium whose diagnosis was made eleven months after its insertion during a caesarean section, associated with a large painful right ovarian cyst. The diagnosis was suspected on pelvic ultrasound and then confirmed during exploratory laparotomy. A cystectomy with removal of the complete IUD was performed and histological analysis of the cyst concluded that there was a serous cystadenoma of the right ovary (benign ovarian tumor). The post-operative follow-up was simple.